THE PLACE AND SIGNIFICANCE OF KHOJAGON-NAQSHBANDIY IDEALS IN BUILDING THE THIRD RENAISSANCE FOUNDATION IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article analyzes from a philosophical point of view the idea of tolerance in the teachings of Khojagon-Naqshbandiyya in building the foundation of the third renaissance in New Uzbekistan, which aims to instill purity, tolerance and goodness in the hearts of people. The call of the representatives of Khojagon-Naqshbandiyya in their teachings to always live in tolerance, to do good to everyone as much as possible, to be kind and compassionate, and their views on other moral qualities are also such ideas of universal importance, such as restraining the ego, strengthening the will, and self-reeducation.